1999
DOI: 10.1292/jvms.61.1215
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Cell Proliferation in the Ductus Arteriosus and the Descending Aorta, and Effects of Enalapril on SMC Proliferation in Perinatal Rats.

Abstract: ABSTRACT. This study was carried out to determine the proliferation profile of the smooth muscle cells (SMC) in the media of the ductus arteriosus (DA) and the descending aorta (Ao), and to examine the effects of the angiotensin-converting enzyme inhibitor enalapril on the proliferation of these cells in perinatal rats. The proliferating cell nuclear antigen (PCNA) index of the DA peaked in 19-day-old fetuses at 75%, and the index significantly declined in 20-day-old fetuses. The PCNA index of the Ao showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Ang II has been implicated as a mediator in the processes of DA remodeling due to its proliferative effects 17-19. To determine whether DAPT attenuates Ang II-induced DASMC proliferation, we first examined the viability of PASMCs by the MTT assay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ang II has been implicated as a mediator in the processes of DA remodeling due to its proliferative effects 17-19. To determine whether DAPT attenuates Ang II-induced DASMC proliferation, we first examined the viability of PASMCs by the MTT assay.…”
Section: Resultsmentioning
confidence: 99%
“…For example, our recent study has demonstrated that through reducing ROS production, a new generation calcium channel blocker can inhibit proliferation and migration of aortic vascular SMCs 18. We also found that anti-proliferative and anti-migratory effects of B-type natriuretic peptide on PASMCs are associated with reduced ROS production by mitochondria and NADPH oxidase 17. How Notch signaling affects the redox state has not been well understood.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, the expression of SM2 was observed only in the SMCs of fetal DA in rabbits [14] and mice [9]. Although the expression of SM2 in the DA has not been studied in rats, SMCs of the DA in 18-and 19-day-old fetuses showed high levels of proliferating activity as revealed by a frequency of the proliferating cell nuclear antigen-positive cells [23]. The high level of proliferating activity of the SMCs was dramatically decreased in the DA of 20-and 21-day-old fetuses [23], suggesting that 19 days of gestation may be the critical stage for the maturation of the DA.…”
Section: Discussionmentioning
confidence: 98%
“…Although the expression of SM2 in the DA has not been studied in rats, SMCs of the DA in 18-and 19-day-old fetuses showed high levels of proliferating activity as revealed by a frequency of the proliferating cell nuclear antigen-positive cells [23]. The high level of proliferating activity of the SMCs was dramatically decreased in the DA of 20-and 21-day-old fetuses [23], suggesting that 19 days of gestation may be the critical stage for the maturation of the DA. Considering the above together with reports that the endogenous NO production is increased in pregnant rats [10], and then decrease at term [26], we considered that the DA in 19-day-old fetuses might have shown a pronounced response to L-NAME due to both SMC maturation and NO production.…”
Section: Discussionmentioning
confidence: 99%